Relasi Gaya Arsitektur dengan Kebudayaan Jawa pada Bangunan Gereja Puhsarang - Yasyafa Prada Zein Giri Swana; Latifah Arifiyani (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
In the following qualitative research, we identified the relationship of architectural styles based on Javanese Culture. The church displays a unique form of architectural acculturation from the church in general which adheres to the European Gothic style. Based on the results of the analysis, the aesthetics of the building combine the architectural style of Rome, namely wide-span buildings and flat domes with local Javanese architecture. The embodiment of Javanese culture is clearly seen in the interior in the form of reliefs and brick materials. The concept of space also puts Javanese architecture in the form of a courtyard without chairs like a Javanese Joglo house. The acculturation functions as an image of local culture so that it is maintained and makes the congregation feel comfortable and dissolve with the atmosphere of the place of worship. The presence of local cultural elements in the church building also shows respect for the values of traditional wisdom without losing the identity of Christianity itself. In addition, the combination of architecture shows that houses of worship can be designed as an inculturative space that is able to bridge the spiritual needs as well as the emotional needs of the congregation. Thus, the church building is not only a place of worship, but also a symbol of harmony between faith and culture in people's lives.